Assessment of the effects of hydrogen water on human gingival fibroblast cell culture in patients with chronic periodontitis - Akanksha Bhatt; Aarati Nayak; Kishore Bhat; Chetana Bogar; Ranganath Nayak; Sachita Naik (Wolters Kluwer Medknow Publications, 2023)
Background: Activated inflammatory cells produce reactive oxygen species (ROS) to eliminate pathogens. Under normal conditions, the pathogens are taken care of, and tissues are repaired. However, in periodontal disease, persistent inflammation causes increased ROS release and impaired healing. Therefore, removal of overproduced ROS using antioxidants is necessary. Hydrogen water has an antioxidative effect on cells and impedes oxidative stress-related disorders. Aim: To study the effect of hydrogen water on cell viability, migration, and its antioxidative potential in fibroblasts obtained from chronic periodontitis patients. Materials and Methods: The gingival tissue samples were obtained from 26 subjects (13 periodontally healthy individuals and 13 chronic periodontitis patients) and processed. The human gingival fibroblasts were cultured and the assays were commenced once adequate growth was detected. The effect of hydrogen water on cell viability was checked by neutral red assay, while the migration potential was assessed by transwell migration assay. The antioxidative potential of hydrogen water was evaluated by CUPRAC assay. Statistical Analysis: Intergroup comparison was done using Mann-Whitney U-test. Intragroup comparison was done using Wilcoxon signed-rank test. Results: Hydrogen water was nontoxic to the fibroblasts at 24 h and 48 h. The intergroup comparison of the cell viability between hydrogen water-treated periodontally healthy gingival fibroblasts (HF) and fibroblasts from patients with chronic periodontitis (CF) showed a statistically significant (P = 0.00) difference at 24 h and 48 h. Hydrogen water also positively influenced the migratory capacity. Hydrogen water-treated fibroblasts obtained from chronic periodontitis patients showed more migration in comparison to the healthy group (P = 0.00). Hydrogen water showed an antioxidative potential. The maximum potential was seen in relation to the fibroblasts obtained from chronic periodontitis patients at 48 h. Conclusion: Hydrogen water was nontoxic, increased the migratory capacity, and showed an antioxidative potential on human fibroblasts obtained from periodontally healthy individuals and patients with chronic periodontitis.